Determinants of construction enterprises' performance: Empirical study from Nepal - Lamichhane, Basu Dev; Lama, Padam Bahadur; Timilsina, Surya Prasad (YAYASAN MITRA PERSADA NUSANTARA, 2025)
The purpose of this study is to investigate the determinants of business performance of construction firms in Nepal. The determinants considered in this study are financial conditions (FC), climatic conditions (CC), political conditions (PC), and regulatory provisions (RP). Similarly, the outcome variable is the business performance (BP) of construction firms in Nepal. The study used a quantitative approach to investigate the formulated hypotheses. This study utilized survey questionnaires of 216 (61.53 percent) respondents as useful questionnaires out of 351 distributed questionnaires. Thus, primary sources of data were used adopting purposive sampling methods. The statistical tools used in the study were descriptive and interferential analysis. The finding of the study showed a positive and significant influence of financial conditions, climatic conditions, political conditions, and regulatory provisions on the business performance of firms of construction enterprises in Nepal. The findings of this study are useful to construction business owners, small and micro-entrepreneurs (SMEs), policymakers, banks and financial institutions (BFIs), regulators, and other stakeholders.